Pengaruh Aksesibilitas dan Fasilitas terhadap Keputusan Berkunjung Wisatawan di Destinasi Wisata Sarasah Tanggo Kabupaten Lima Puluh Kota - Zihan Permana; Nini Sumarni (ARZUSIN, 2026)
Tourists’ decisions to visit a destination are influenced by various factors, including accessibility and available facilities. This study aimed to identify and analyze the influence of accessibility and facilities, both partially and simultaneously, on tourists’ visiting decisions at the Sarasah Tanggo Tourist Destination. This study used a quantitative approach with descriptive research and field research designs. Data were collected through questionnaires involving 96 respondents and were then analyzed using multiple linear regression, the coefficient of determination test, t-test, and F-test. The results showed that accessibility and facilities simultaneously influenced tourists’ visiting decisions. The Adjusted R Square value of 0.187 indicated that accessibility and facilities contributed 18.7% to visiting decisions, while the remaining 81.3% was influenced by other variables not examined in this study. Partially, accessibility did not have a significant effect on visiting decisions, as indicated by the calculated t-value of -0.354 < the t-table value of 1.985 and a significance value of 0.724 > 0.05. Conversely, facilities had a significant effect on visiting decisions, with a calculated t-value of 4.490 > the t-table value of 1.985 and a significance value of 0.000 < 0.05. The F-test results showed that accessibility and facilities simultaneously had a significant effect on visiting decisions, with a calculated F-value of 11.279 > the F-table value of 3.09 and a significance value of 0.000 < 0.05. Thus, facilities are a more dominant factor in influencing tourists’ visiting decisions, while improving accessibility still needs to be considered as part of comprehensive tourist destination development.